Deletion of a pathogenic mutation-containing exon of COL7A1 allows clonal gene editing correction of RDEB patient epidermal stem cells - Mencía, Ángeles; Chamorro, Cristina; Bonafont, Jose; Duarte, Blanca; Holguin, Almudena; Illera, Nuria; Llames, Sara G.; Escámez, Maria José; Haußer-Siller, Ingrid; Del Río, Marcela; Larcher, Fernando; Murillas, Rodolfo (Molecular therapy. Nucleic Acids, 2018)
Recessive dystrophic epidermolysis bullosa is a severe skin fragility disease caused by loss of functional type VII collagen at the dermal-epidermal junction. A frameshift mutation in exon 80 of COL7A1 gene, c.6527insC, is highly prevalent in the Spanish patient population. We have implemented gene-editing strategies for COL7A1 frame restoration by NHEJ-induced indels in epidermal stem cells from patients carrying this mutation. TALEN nucleases designed to cut within the COL7A1 exon 80 sequence were delivered to primary patient keratinocyte cultures by non-integrating viral vectors. After genotyping a large collection of vector-transduced patient keratinocyte clones with high proliferative potential, we identified a significant percentage of clones with COL7A1 reading frame recovery and Collagen VII protein expression. Skin equivalents generated with cells from a clone lacking exon 80 entirely were able to regenerate phenotypically normal human skin upon their grafting onto immunodeficient mice. These patient-derived human skin grafts showed Collagen VII deposition at the basement membrane zone, formation of anchoring fibrils, and structural integrity when analyzed 12 weeks after grafting. Our data provide a proof-of-principle for recessive dystrophic epidermolysis bullosa treatment through ex vivo gene editing based on removal of pathogenic mutation-containing, functionally expendable COL7A1 exons in patient epidermal stem cells.
Gesehen am 30.03.2020